Enhanced Removal of Phosphorus from Aqueous Solutions by Cation-Modified Hydrochar - Kamyaporn Wutthipattarathorn; Usarat Thawornchaisit; Suwannee Janyapoon (Trends in Sciences, 2023)
In this study, cassava stem-derived hydrochar was modified with sodium hydroxide (NaOH) treatment, followed by loading of minerals, was used to prepare cation-modified hydrochars with enhanced phosphate removal ability. Cassava stems were converted to hydrochar by hydrothermal carbonization at 240 °C for 60 min, then it was soaked in 2 M NaOH for 3 h. The NaOH-treated hydrochars were then loaded with iron (Fe), magnesium (Mg) and calcium (Ca). The cassava stems and the derived hydrochars were analyzed for carbon, hydrogen, nitrogen and oxygen content, surface morphology and elemental compositions. Methylene Blue Numbers (MBN) measured surface area and porosity, and pH at the point of zero charge (pHpzc) was determined. Modification with Fe, Mg and Ca improved phosphate removal efficiency of the resulting hydrochars. Treatment of synthetic wastewater containing 50 mg P/L at pH 7 with the dosage of 2 g/L of the cation-modified hydrochars for 360 min showed that phosphate removal efficiency of these modified hydrochars were - Fe-modified 81 %, Mg-modified 66 % and Ca-modified 56 %. When the adsorbent dosage increased to 20 g/L, more than 98 % of phosphate was removed by the hydrochars modified with Fe, Ca and Mg. In the same conditions, phosphate removal efficiency was for the NaOH-treated hydrochars - 89 %, hydrochar derived from cassava steam - 69 % and the starting material - 59 %. The phosphate removal ability of these cation-modified hydrochars increased even when initial phosphorus concentration was increased to 100 mg P/L. This work demonstrated that an abundant agricultural residue, cassava stems, can be converted into effective phosphate adsorbents. HIGHLIGHTS Cassava stem were converted to hydrochar by aqueous carbonization at elevated temperature and pressure - hydrothermal carbonization (HTC) Sequential steps of alkali treatment and chemical modification, following HTC, were used to improve the phosphate removal ability of the cassava stem-derived hydrochar Loading of minerals (Fe, Mg and Ca) was a vital way to increase the adsorption of phosphates on hydrochar Phosphorus removal efficiency of Fe-loaded hydrochar was better than Mg- and Ca-loaded hydrochars Cation-modified hydrochars showed good phosphate removal ability over a wider concentration range GRAPHICAL ABSTRACT
Keywords: Phosphorus and nutrient management